Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Castillo Cacsire, Jorge Pedro (2019)
This deliverable describes the strategic planning proposed for the Fast Retailing corporation in its entry with the UNIQLO brand to the Fast Fashion sector in Peru.